CONSTRUCTING MASCULINITY AND FEMININITY IN UZBEK–ENGLISH ONLINE MEMES: A DISCURSIVE APPROACH - Qudratullayeva, Muniraxon (QO‘QON UNIVERSITETI XABARNOMASI, 2026)
This article examines how masculinity and femininity are constructed and represented in Uzbek–English online memes through a discursive lens. Online memes function as multimodal discourse units that reflect and reproduce social norms, gender ideologies, and cultural values. Drawing on critical discourse analysis and gender studies, the study analyzes a corpus of Uzbek and English-language memes collected from social media platforms such as Instagram, Telegram, and Twitter. The findings reveal that while English-language memes often emphasize individualism, irony, and gender role subversion, Uzbek-language memes tend to reinforce traditional gender norms grounded in collectivism, family hierarchy, and moral expectations. The study highlights how bilingual and hybrid memes negotiate gender identities at the intersection of global digital culture and local sociocultural values. Pedagogical and sociolinguistic implications are discussed, particularly in relation to intercultural communication and digital literacy.